"Found Down" Compartment Syndrome: Experience from the Front Lines of the Opioid Epidemic. (4th September 2019) - Parzych, Lydia; Jo, Jacob; Diwan, Amna; Swart, Eric
Abstract : Background: With the worsening of the opioid epidemic, there has been an increasing number of cases in which patients are "found down" following a drug overdose and develop a crush injury resulting in muscle necrosis, rhabdomyolysis, and elevated compartment pressures in a unique presentation of compartment syndrome. The purpose of the present study is to summarize our experience at a trauma center in a region with a high endemic rate of opiate abuse to provide guidance for the management of patients with "found down" compartment syndrome. Methods: We performed a retrospective review of the records of patients who had been found unconscious as the result of overdose, with findings that were concerning for compartment syndrome, and had been managed with fasciotomy or observation at the discretion of the surgeon. The patients were divided into 3 groups based on presentation (partial deficits, complete deficits, or unexaminable), and the operative findings, hospital course, laboratory values, and functional status were compared between the groups. Results: Over 12 years, we identified 30 "found down" patients who had an examination that was concerning for compartment syndrome. Twenty-five patients were managed with fasciotomy; this group required an average of 4.2 operations and had a 20% infection rate and a 12% amputation rate. Lactate, creatine phosphokinase, and creatinine levels typically were elevated but did not correspond with muscle viability or return of function. At the time of initial debridement, 56% of patients had muscle that appeared nonviable, although muscle function returned in 28% of the patients who had questionable viability. Four patients had no motor or neurological function on initial examination, and none had meaningful return of function at the time of the latest follow-up. Of the 10 patients who had partial neurological deficits at the time of presentation and underwent fasciotomy, over half (70%) had some improvement in ultimate function. Conclusions: Patients who are "found down" following an opiate overdose with crush injuries resulting in compartment syndrome have a high surgical complication rate and poor recovery of function. The limited data from the present study suggest that those with absent function at the time of presentation are unlikely to gain function after fasciotomy, and the risk-benefit ratio of fasciotomy in this patient population may be different from that for patients with traumatic compartment syndrome. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.